(untitled) (Bangladesh Journal of Agricultural Research, 2023)
The hog plum (Spondias mombin) is locally known as Amra is very popular fruit in Bangladesh. It is very delicious fruit and sources of Vitamin C. The purpose of this study is to identify the importance of the attributes of hog plum on its price. A total of 121 respondents were interviewed to identify the attributes of hog plum purchase decision using both OLS and robust regression models. Results show that quantity, whole fresh and blemish free are important attributes for hog plum purchase decision. Quantity, blemish free and traceability are significantly important attributes for low income consumer groups whereas quantity and whole fresh are significantly important attributes for high income consumer groups. The implication of the study is that proper hog plum farming system and its marketing activities design are necessary for making it a profitable business. Bangladesh J. Agril. Res. 46(1): 107-116, March 2021